2023
DOI: 10.1002/adma.202303432
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Microenvironment‐Responsive Self‐Assembly Nanoreactors for All‐Stage Biofilm Associated Infection through Bacterial Cuproptosis‐like Death and Macrophage Re‐Rousing

Abstract: Bacterial biofilm‐associated infections (BAIs) are the leading cause of prosthetic implant failure. The dense biofilm structure prevents antibiotic penetration, while the highly acidic and H2O2‐rich biofilm microenvironment (BME) dampens the immunological response of antimicrobial macrophages. Conventional treatments that fail to consistently suppress escaping planktonic bacteria from biofilm result in refractory recolonization, allowing BAIs to persist. Herein, a BME‐responsive copper‐doped polyoxometalate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 55 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…Besides, the persistent bacteria located in the inner layer of the biofilm displayed metabolic inactivity state, which caused incomplete eradication of bacteria and the relapse of biofilm infections. Activating innate immunity to eliminate the persistent bacteria with inactive metabolism was an effective strategy to prevent infection recurrence. The polarization effect of Fe 3 O 4 @Bi 2 S 3 on RAW264.7 macrophages was carried out to determine the immune regulatory function.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the persistent bacteria located in the inner layer of the biofilm displayed metabolic inactivity state, which caused incomplete eradication of bacteria and the relapse of biofilm infections. Activating innate immunity to eliminate the persistent bacteria with inactive metabolism was an effective strategy to prevent infection recurrence. The polarization effect of Fe 3 O 4 @Bi 2 S 3 on RAW264.7 macrophages was carried out to determine the immune regulatory function.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, self-assembly nanomaterials have also been advocated in TAMs’ reprogramming due to their high drug loading quantity, modifiability, and excellent biocompatibility. Xie et al reported a DNA nanocluster that was self-assembled by double-stranded DNA vectors with loaded unmethylated cytosine-phosphate-guanine (CpG) oligonucleotide (ODN) . The loaded CpG-ODN can bind with toll-like receptor 9 (TLR9) to stimulate immunocompetent cells for TAMs’ pro-inflammatory polarization and cancer immunotherapy. , High condensation of DNA nanoclusters could effectively protect CpG-ODNs from digestion and degradation by nuclease.…”
Section: Various Nanomaterials-mediated Tams’ Polarizationsmentioning
confidence: 99%
“…Activated macrophages and dendritic cells foster the activation and expansion of T cells and release pro-inflammatory factors and stress proteins, facilitating immune cell-mediated killing of cancer cells. [37] However, an excessive inflammatory response may result in adverse treatment effects, causing infiltration and damage of immune cells in normal tissues, thus compromising the therapeutic outcome. Hence, suppressing PTT-induced inflammation may minimize harm to normal tissues and enhance treatment effectiveness.…”
Section: In Vivo Anti-inflammatory Effects Of V 2 C Mxenzymementioning
confidence: 99%